ISLAMIC MARRIAGE COUNSELLING MODEL FOR STUNTING PREVENTION AND FAMILY EDUCATION - Salim, Amil; Annur, Saipul; Muslim, Muslim; Umida, Baltaeva (Conciencia, 2025)
Stunting prevention requires a preventive educational approach grounded in Islamic values, particularly through premarital family preparation. This study examines an Islamic marriage counselling model implemented by the Office of Religious Affairs (KUA) as a form of preventive Islamic education aimed at strengthening family education and reducing the risk of stunting. The counselling model positions premarital guidance (bimbingan perkawinan) as an early dakwah based educational strategy that integrates Islamic teachings, moral responsibility, and practical knowledge for building healthy families. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving religious counsellors, KUA officials, prospective brides and grooms, and related stakeholders in Penukal Abab Lematang Ilir District. Data analysis was conducted using thematic analysis, including data reduction, categorization, interpretation, and triangulation to ensure validity. The findings show that Islamic marriage counselling functions as an effective preventive tool in Islamic education by embedding values of maslahah, parental responsibility, reproductive ethics, balanced nutrition, and family planning within a religious framework. This approach enhances couples’ awareness and readiness to establish healthy, resilient, and child-friendly families. However, the programme faces challenges related to limited counselling duration, varying levels of understanding of stunting, and insufficient human resources and facilities. The study concludes that strengthening Islamic marriage counselling as a structured educational intervention is essential for effective stunting prevention and sustainable family education.